A systematic review of COVID-19 effects on agri-food chains in Latin America - Roco, Lisandro; Fischer, Andreass; Grisa, Catia; García, Francisco; Sanguinet, Eduardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The rise of the COVID-19 pandemic generated large effects on global supply chains. These effects are especially relevant in agriculture, as they compromised food security. The present study is a systematic review of peer-reviewed scientific literature to understand the effects of the pandemic on agro-food chains and links in Latin America. The documented effects are mainly negative (81.5 %) and translated into impacts on production systems (32.3 %) and markets (24.6 %). It was reported that the impacts on production were due to difficulties in labor mobility, interruption of the supply chain, closure of external markets and increased transportation costs. Transportation was the link with the most difficulties due to restrictions on mobilization, even though it was the least referenced. There were negative impacts on processing, due to the shortage of raw materials and the interruption or closure of industries. On the other hand, some positive effects were reported, such as the development of local markets, the emergence of alternative products and digital markets with direct home delivery, as well as a shift towards healthy consumer habits. Agricultural policy makers should take these results into account when proposing strategies to develop more resilient agrifood chains to face challenges such as those caused by the Covid-19 pandemic.